2015
DOI: 10.1088/0957-4484/27/1/015702
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced resistive switching in forming-free graphene oxide films embedded with gold nanoparticles deposited by electrophoresis

Abstract: Forming-free resistive random access memory (ReRAM) devices having low switching voltages are a prerequisite for their commercial applications. In this study, the forming-free resistive switching characteristics of graphene oxide (GO) films embedded with gold nanoparticles (Au Nps), having an enhanced on/off ratio at very low switching voltages, were investigated for non-volatile memories. The GOAu films were deposited by the electrophoresis method and as-grown films were found to be in the low resistance stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 39 publications
2
27
0
Order By: Relevance
“…In the above expression, is the reduced Planck's constant, mnormale* is the effective mass, E is the local electric field, x is the distance among trap centers, q e is the elementary charge of electrons, E b the interface barrier, and E t the trap energy below the conduction band (≈0.3 eV for oxygen vacancies) . We remark that NCs charging has been also confirmed experimentally in similar structures . This interpretation could also account for the weak capacitance switching of 3 nm Ta NCs samples, since a lower injected current will impose smaller capacitance values.…”
Section: Resultssupporting
confidence: 51%
“…In the above expression, is the reduced Planck's constant, mnormale* is the effective mass, E is the local electric field, x is the distance among trap centers, q e is the elementary charge of electrons, E b the interface barrier, and E t the trap energy below the conduction band (≈0.3 eV for oxygen vacancies) . We remark that NCs charging has been also confirmed experimentally in similar structures . This interpretation could also account for the weak capacitance switching of 3 nm Ta NCs samples, since a lower injected current will impose smaller capacitance values.…”
Section: Resultssupporting
confidence: 51%
“…For samples treated with HCl solution, RS is governed by metal cations (Cu + , W + ) and migration of oxygen groups dominates RS in N 2 H 4 treated device (as confirmed by adopting different kinds of electrodes). Additionally, Au‐doped RRAM is also reported in reference . The doping process is realized by simply mixing Au nanoparticles (10–15 nm in diameter) into GO solution and being treated by electrophoresis.…”
Section: Materials Modulationmentioning
confidence: 99%
“…RRAM devices based on oxide have good switching characteristics, but still there are two major downsides with these memories: first one is the need of an initial forming voltage [68][69][70] to initiate the switching mechanism, which is detrimental to device performance, however, this issue can be resolved by manipulating the deposition and growth process and the other problem is the uncontrolled position of conductive channels formation during repetitive applied bias. To address the problem of initial forming in graphene oxide (GO)-based devices, we adopted the method of electrophoresis to deposit the device structure [71]. Reports have shown that the graphene oxide films grown by electrophoresis are conducted or reduced in nature [72,73].As the oxygen functional groups attached to its basal plane get removed, the graphene oxide films become semiconducting having localized π-π electrons network.…”
Section: Nanoparticles Embedded Graphene Oxide Rram Devices For Low Omentioning
confidence: 99%
“…A colloidal suspension of GO with Au Nps was obtained by sonication. The films were deposited by electrophoresis process using the sonicated GO with Au Nps (GOAu) solution [71]. Electrophoresis was performed using a homebuilt assembly with a pair of ITO/glass as electrodes and a Keithley current source.…”
Section: Nanoparticles Embedded Graphene Oxide Rram Devices For Low Omentioning
confidence: 99%